A multiplex HRMS assay for quantifying selected human plasma bile acids as candidate OATP biomarkers. (11th May 2018) - Rago, Brian; Tierney, Brendan; Rodrigues, A David; L Holliman, Christopher; Ramanathan, Ragu
Aim: Selected bile acids (BAs) in plasma have been proposed as endogenous probes for assessing drug–drug interactions involving hepatic drug transporters such as the organic anion-transporting polypeptides (OATP1B1 and OATP1B3).Materials & methods: Plasma extracts were analyzed for selected BAs using a triple TOF API6600 high-resolution mass spectrometer.Results: Glycodeoxycholic acid 3-sulfate, glycochenodeoxycholic acid 3-sulfate, glycodeoxycholic acid 3-O-β-glucuronide and glycochenodeoxycholic acid 3-O-β-glucuronide are presented as potential OATP1B1/3 biomarkers.Conclusion: Six BAs are quantified in human plasma using a multiplexed high-resolution mass spectrometry method. Glycodeoxycholic acid 3-sulfate and glycodeoxycholic acid 3-O-β-glucuronide are proposed as potential biomarkers based on observed four- to fivefold increase in plasma AUC (vs placebo), following administration of a compound known to present as an OATP1B1/3 inhibitor in vitro .